Triazine-based organic polymer-catalysed conversion of epoxide to cyclic carbonate under ambient CO2 pressure - Biswas, Tanmoy; Halder, Arjun; Paliwal, Khusboo S.; Mitra, Antarip; Tudu, Gouri; Banerjee, Rahul; Mahalingam, Venkataramanan (Chemistry-An Asian Journal, 2020)
In this work we have achieved epoxide to cyclic carbonate conversion using a metal-free polymeric catalyst under ambient CO2 pressure (1.02 atm) using a balloon setup. The triazine containing polymer (CYA-ANIS) was prepared from cyanuric chloride (CYA-Cl) and o-dianisidine (ANIS) in anhydrous DMF as solvent by refluxing under the N-2 gas environment. The presence of triazine and amine functional groups in the polymer results in the adsorption of CO2 up to 7 cc/g at 273 K. This inspired us to utilize the polymer for the conversion of a series of functionalised epoxides into their corresponding cyclic carbonates in the presence of tetrabutyl ammonium iodide (TBAI) as co-catalyst. The product has wide range of applications like solvent in lithium ion battery, precursor for polycarbonate, etc. The catalyst was efficient for the conversion of different mono and di-epoxides into their corresponding cyclic carbonates under atmospheric pressure in the presence of TBAI as co-catalyst. The study indicates that epoxide attached with electron withdrawing groups (like, CH2Cl, glycidyl ether, etc.) displayed better conversion compared to simple alkane chain attached epoxides. This is mainly due to the stabilization of electron rich intermediates produced during the reaction (e. g. epoxide ring opening or CO2 incorporation into the halo-alkoxide anion). This catalyst mixture was capable to maintain its reactivity up to five cycles without losing its activity. Post catalytic characterization clearly supports the heterogeneous and recyclable nature of the catalyst.
Keywords: CO2 fixation; cyclic carbonates; epoxides; Heterogeneouscatalyst; metal free catalyst; Triazinepolymer